Respuesta :

Answer:

left 2 units and up 6 units

Step-by-step explanation:

f(x) = (x + 2)^4 + 6

y = f(x) + C  C > 0 moves it up

So this moves it up 6 units

y = f(x + C) C > 0 moves it left

So this moves it to the left 2 units

The parent function g(x) is shifted to the left 2 units and up 6 units to get the function f(x).

What is a function?

Function is a type of relation, or rule, that maps one input to specific single output.

Given function;

f(x) = (x + 2)^4 + 6

y = f(x) + C  

C > 0 moves it up

So, this moves it up 6 units.

y = f(x + C)

C > 0 moves it left

So, this moves it to the left 2 units.

Learn more about function here:

https://brainly.com/question/2253924

#SPJ2